GGE biplot based assessment of yield stability, adaptability and mega-environment characterization for hybrid pigeonpea (Cajanus cajan) - SRIVASTAVA, RAKESH K; RATHORE, ABHISHEK; VALES, M ISABEL; KUMAR, R VIJAYA (The Indian Journal of Agricultural Sciences, 2014)
GGE biplot methodology is a powerful tool to study relationship among test environments (E), genotypes (G) and genotype-by-environment interaction (GE). Present study was conducted on 10 short-duration genotypes in five test environments for two years, and 16 medium-duration genotypes in six test locations for three years in randomized complete block design with two replications. In short-maturity group three mega-environments (ME) were found—ME1 comprised of Phaltan, Patancheru and Hyderabad1; ME2 and 3 constituted Jalna and Aurangabad, respectively. In scenario of limited resources, Patancheru may be a good testing location for general adaptability of short-duration hybrids, while Aurangabad and Hyderabad1 may be right environments for testing specific adaptation of short-duration cultivars in pigeonpea. ICPH 2433 was a winning genotype in ME1 in terms of high yield and stability. In medium-maturity group, two MEs were observed. Jalna, Jalna 1, Parbhani and Hyderabad grouped together as ME1, while Patancheru and Phaltan formed the second mega-environment (ME2). Parbhani was found to be most representative of all the six test locations. Jalna (ME1) and Phaltan (ME2) produced longest environment vectors, and hence may be regarded as highly discriminating. In medium- maturity group ICPH 2673 was found to be stable and high-yielding genotype for ME1.